Nexus between CSR and Firm Performance: Moderating Effect of Ownership Concentration - Van Nguyen (Arthatama: Journal of Business Management and Accounting, 2019)
The primary objective of this study is to examine the association between CSR activities and firm performance in the context of Vietnam. This study also aims to determine the moderating effect of ownership concentration on the association between CSR activities and firm performance. This research has followed a quantitative design given the fact that companies’ CSR initiatives and performance has been measured and tested for relationship and impact. The data for this research paper has been obtained from thirty firms operating in Vietnam for the period ranging from 2015 to 2019. Generalised Least Squares (GLS) is used as the major analysis technique in order to understand the moderating role of ownership concentration in explaining the impact of CSR on company performance. It was found that company’s expenditure on CSR activities is positively reflected in their financial performance. The secondary studies have also incorporated the role of ownership concentration in explaining the relationship of CSR and firm performance. However, the findings of this study have suggested otherwise as no significant moderating role of ownership concentration was found in explaining the impact of CSR on firm performance in the case of Vietnamese firms.